Plant growth-promoting rhizobacterium Bacillus megaterium modulates the expression of antioxidant-related and drought-responsive genes to protect rice (Oryza sativa L.) from drought - Lee, Sanghun; Kim, Jung-Ae; Song, Jeongsup; Choe, Seonbong; Jang, Geupil; Kim, Yangseon (Frontiers in Microbiology, 2024)
Global climate change poses a significant threat to plant growth and crop yield and is exacerbated by environmental factors, such as drought, salinity, greenhouse gasses, and extreme temperatures. Plant growth-promoting rhizobacteria (PGPR) help plants withstand drought. However, the mechanisms underlying PGPR–plant interactions remain unclear. Thus, this study aimed to isolate PGPR, Bacillus megaterium strains CACC109 and CACC119, from a ginseng field and investigate the mechanisms underlying PGPR-stimulated tolerance to drought stress by evaluating their plant growth-promoting activities and effects on rice growth and stress tolerance through in vitro assays, pot experiments, and physiological and molecular analyses. Compared with B. megaterium type strain ATCC14581, CACC109 and CACC119 exhibited higher survival rates under osmotic stress, indicating their potential to enhance drought tolerance. Additionally, CACC109 and CACC119 strains exhibited various plant growth-promoting activities, including phosphate solubilization, nitrogen fixation, indole-3-acetic acid production, siderophore secretion, 1-aminocyclopropane-1-carboxylate deaminase activity, and exopolysaccharide production. After inoculation, CACC109 and CACC119 significantly improved the seed germination of rice (Oryza sativa L.) under osmotic stress and promoted root growth under stressed and non-stressed conditions. They also facilitated plant growth in pot experiments, as evidenced by increased shoot and root lengths, weights, and leaf widths. Furthermore, CACC109 and CACC119 improved plant physiological characteristics, such as chlorophyll levels, and production of osmolytes, such as proline. In particular, CACC109- and CACC119-treated rice plants showed better drought tolerance, as evidenced by their higher survival rates, greater chlorophyll contents, and lower water loss rates, compared with mock-treated rice plants. Application of CACC109 and CACC119 upregulated the expression of antioxidant-related genes (e.g., OsCAT, OsPOD, OsAPX, and OsSOD) and drought-responsive genes (e.g., OsWRKY47, OsZIP23, OsDREB2, OsNAC066, OsAREB1, and OsAREB2). In conclusion, CACC109 and CACC119 are promising biostimulants for enhancing plant growth and conferring resistance to abiotic stresses in crop production. Future studies should conduct field trials to validate these findings under real agricultural conditions, optimize inoculation methods for practical use, and further investigate the biochemical and physiological responses underlying the observed benefits.